2001
DOI: 10.1080/00365510151067947
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay for N-terminal probrain natriuretic peptide in human plasma

Abstract: Measurement of plasma levels of natriuretic peptides has been used to assess left ventricular dysfunction and prognosis. Recently levels of the N-terminal peptide fragment of the precursor of brain natriuretic peptide have been reported to be present in peripheral plasma and to be increased in chronic heart failure patients. Our aim in this study was to develop a radioimmunoassay for N-terminal proBNP, to compare its plasma concentrations in control subjects and in patients with end-stage heart failure and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 29 publications
4
23
1
Order By: Relevance
“…Immunoassays may nevertheless still detect the intact prohormone and therefore not reflect the actual bioactivity of the secreted peptides. In agreement with this suggestion, patients with congestive heart failure have increased plasma concentrations of immunoreactive N-terminal proBNP, and this immunoreactive material seems to also contain a polypeptide corresponding to the intact precursor (16,39,40 ). Thus, the congestion in heart failure patients may not be ameliorated by the secreted natriuretic peptides.…”
Section: Endocrine Paradox In Heart Failuresupporting
confidence: 59%
See 2 more Smart Citations
“…Immunoassays may nevertheless still detect the intact prohormone and therefore not reflect the actual bioactivity of the secreted peptides. In agreement with this suggestion, patients with congestive heart failure have increased plasma concentrations of immunoreactive N-terminal proBNP, and this immunoreactive material seems to also contain a polypeptide corresponding to the intact precursor (16,39,40 ). Thus, the congestion in heart failure patients may not be ameliorated by the secreted natriuretic peptides.…”
Section: Endocrine Paradox In Heart Failuresupporting
confidence: 59%
“…It is therefore important to realize that the preproBNP molecule does not exist in real life but is only as a theoretical concept. In contrast, proBNP is likely an existing small protein, the existence of which to date has been indicated by chromatographic studies and sequence-specific immunoassays (16,39,40 ). However, the actual precursor has not been identified on a molecular level, nor have the fragments thereof, apart from the C-terminal BNP-32 peptide itself (10 ).…”
Section: Structure Of Probnpmentioning
confidence: 99%
See 1 more Smart Citation
“…NT-proBNP assays theoretically should show 100% cross-reactivity with proBNP. Furthermore, intact proBNP has been described in human plasma, and oligomerization probably occurs (11 ). Assays for BNP and NT-proBNP may differ in their susceptibility to analytical interferences.…”
Section: Information Requiredmentioning
confidence: 99%
“…High BNP levels in patients with chronic heart failure (CHF) often indicate poor ventricular function and a worse prognosis, but studies have shown that in some patients with severe chronic heart failure the plasma BNP level is normal [8,9]. In clinical practice, with quality laboratory resources, BNP has been introduced to diagnosis, prognosis and as a guide for treatment [10][11][12][13][14][15]. In this study, 57 patients with severe CHF seen at our hospital from December 2002 to October 2009, were studied, focusing on plasma levels of BNP, clinical features and prognosis.…”
mentioning
confidence: 99%